Gender Justice and Contemporary Qur’anic Interpretation: Insights from Ngaji KGI in Indonesia - Aisyah, Aisyah; Kusmana, Kusmana (QOF, 2025)
Ngaji Keadilan Gender Islam (KGI) is a discussion forum initiated by Nur Rofiah in response to the lack of accessible Qur’anic interpretations that promote gender justice. This article aims to analyze how Ngaji KGI represents the practice of living Qur’an within Islamic feminist discourse and contributes to the dynamics of gender justice in Indonesia. Using a qualitative approach with the type of field research and data through interviews, observation, and documentation. The findings show that Ngaji KGI actively constructs Qur’ānic interpretations that prioritize women’s lived experiences based on the principle of women's haqiqi (real) justice. The forum not only shifts perceptions of women’s roles but also utilizes digital platforms to disseminate its values. Ngaji KGI strives to ground and bring to life the values of the Qur’an related to Islamic gender justice through contextual and participatory interpretation in social reality. These findings enrich the discourse of contemporary Islamic feminism and demonstrate the importance of the role of the community in developing gender-just interpretations.